Characterization of genetic diversity of Trachemys dorbigni and Phrynops hilarii - Guidetti, Brenda Yamile (2015)
The utilization of RAPD and ISSR molecular markers is proposed to initiate studies of genetic variability in Phrynops hilarii and Trachemys dorbigni, two species of fresh water turtles distributed in South America. Three primers of RAPD and four of ISSR were selected and the amplified products of these markers were evaluated by electrophoretic runs in agarose and polyacrylamide gels. The levels of heterozygosity, Shannon index and different allele numbers were slightly higher in P. hilarii for both types of markers. Levels of polymorphism were also higher in P. hilarii than T. dorbigni and both were elevated compared to those recorded for other species. The fact that similar results were obtained with both types of markers for all estimates of diversity highlights the usefulness and validity of the RAPD technique. The molecular markers used were found potentially useful for analysing future temporal and spatial distribution of genetic diversity in both species, expanding scales work.